Stable Pincer Gold(III)‐TADF Emitters with Extended Donor–Acceptor Separation for Efficient Vacuum‐Deposited OLEDs with Operational Lifetime (LT95) up to 3831 h at 1000 cd m−2 - Hui‐Xing Shu; Shuo Xu; Wai‐Pong To; Gang Cheng; Chi‐Ming Che (Advanced Science, 2025)
Abstract Although gold‐TADF (thermally activated delayed fluorescence) emitters have attractive prospects as next‐generation practical OLED emitters, the performance of OLEDs utilizing gold(I)‐ and gold(III)‐TADF emitters lags behind the requirements of practical applications, and device lifetime has become a bottleneck. Here, novel pincer gold(III)‐TADF emitters that are easily fabricated with tunable donor and acceptor ligands are presented. These pincer gold(III)‐TADF emitters exhibit an extended molecular π‐distance along the transition dipole moment, resulting in a significant reduction in the electron exchange energy between the S1 and T1 excited states, thus narrowing the singlet–triplet energy gap (ΔEST). The combination of small ΔEST and heavy‐atom (Au, S) effect greatly enhances spin‐flip dynamics and produces efficient TADF (photoluminescence quantum yields up to 90%) with high radiative decay rate constants (kr up to 106 s−1), and short lifetimes (τ less than 1.2 µs) in thin films at room temperature. Vacuum‐deposited OLEDs based on these gold(III)‐TADF emitters demonstrate impressive stability, achieving i) a high maximum external quantum efficiency (EQEmax) of up to 22.2%, and ii) a record‐ long operational lifetime (LT95) of 3831 h at an initial luminance of 1000 cd m−2. This excellent durability makes the pincer gold(III)‐TADF emitter a promising and competitive alternative to iridium and platinum emitters for practical OLED applications.